New Insights into the Biosynthesis Pathway of Polyketide Alkaloid Argimycins P in Streptomyces argillaceus - Ye, Suhui; Braña, Alfredo F.; González-Sabín, Javier; Morís, Francisco; Olano, Carlos; Salas, José A.; Méndez, Carmen (Frontiers in Microbiology, 2018)
Argimycins P are a recently identified family of polyketide alkaloids encoded by the cryptic gene cluster arp of Streptomyces argillaceus. These compounds contain either a piperideine ring, or a piperidine ring which may be fused to a five membered ring, and a polyene side chain, which is bound in some cases to an N-acetylcysteine moiety. The arp cluster consists of eleven genes coding for structural proteins, two for regulatory proteins and one for a hypothetical protein. Herein, we have characterized the post-piperideine ring biosynthesis steps of argimycins P through the generation of mutants in arp genes, the identification and characterization of compounds accumulated by those mutants, and cross-feeding experiments between mutants. Based in these results, a biosynthesis pathway is proposed assigning roles to every arp gene product. The regulation of the arp cluster is also addressed by inactivating/overexpressing the positive SARP-like ArpRI and the negative TetR-like ArpRII transcriptional regulators and determining the effect on argimycins P production, and through gene expression analyses (reverse transcription PCR and quantitative real-time PCR) of arp genes in regulatory mutants in comparison to the wild type strain. These findings will contribute to deepen the knowledge on the biosynthesis of piperidine-containing polyketides and provide tools that can be used to generate new analogs by genetic engineering and/or biocatalysis.